Hubungan Kadar Gula Darah Puasa Dengan Kadar Gula Darah Post- Prandial 2 Jam Pada Lansia Di Rs Hermina Arcamanik - Erna Sari; Restiani Alia Pratiwi (Asosiasi Guru dan Dosen Seluruh Indonesia, 2026)
The increasing prevalence of type 2 diabetes melitus among the erderly is closely linked to a decline in metabolic function. Assessing glycemic status through fasting blood glucose (FBG) and 2-hour postprandial blood glucose (2hPBG) levels is crucial for identifying the progression of diabetes melitus. This study aims to analyze the relationship between fasting blood glucose (FGB) levels and 2-hour postprandial blood glucose(2hPBG) levels the elderly at Hermina Arcamanik Hospital. This is a quantitative study using an observational analytical approach with a cross-sectional design. The sample consisted of 70 respondents selected through purposive sampling. Data analysis utilized univariate and Spearman’s rho bivariate test. The result showed that the majority of participants met the clinical criteria for prediabetes (23%) and type 2 diabetes melitus (67%). Statistical analysis revealed a significant and strong positive correlation between FBG and 2hPBG levels, with a correlation coefficient of r = 0.785 and p = 0.000. In conclusion, there is a strong positive correlation between FBG and 2hPBG levels. Pathophysiologically, an increase in these two parameters indicates pancreatic beta-cell dysfunction and insulin resistance influenced by aging. These findings underscore the importance of comprehensive glycemic screening as the first step in the early identification and monitoring of diabetes melitus risk in.